Analisis Sukuk Pada Keuangan Syariah di Indonesia : Systematic Literature Review - Nurul Ma’rifah Engget; Nisya Adella Jaya; Alim Erdiansah; Asrial; Anzu Elvia Zahara (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The capital market is one of the means used for investment but there are many capital market instruments that contain elements that are not halal (haram) according to Islamic law. This study aims to see Indonesia's position in the Islamic financial market through the role of sukuk. Because considering that Indonesia is a Muslim-majority country and investment in the capital market is the government's effort to encourage and strengthen Indonesia's position on the national and global Islamic financial markets. This research uses a Systematic Literature Review (SLR) approach to journal publications from 2012 to 2022. The results show that research on Islamic finance in Indonesia focuses on 3 topics and trends, namely SBSN, Green Sukuk and Sukuk from an Islamic perspective. And the most frequently used method is the library research method by 50%, the qualitative method by 40% and the Analytic Network Process Problem-Solution Method by 10%.